Gut Commensal Fungi Protect Against Acetaminophen-Induced Hepatotoxicity by Reducing Cyp2a5 Expression in Mice - He, Zhuoen; Zeng, Yunong; Li, Shuyu; Lin, Lizhen; Zhou, Ruisi; Wang, Fangzhao; Yang, Wenjiao; Wu, Yuhao; Yang, Junhao; Chen, Ali; Wang, Zhang; Yang, Hong; et al. (Frontiers in Microbiology, 2022)
Background & Aims Drug-induced liver injury (DILI) is a common cause of acute liver failure and represents a significant global public health problem. When discussing the gut-liver axis, although a great deal of research has focused on the role of gut microbiota in regulating the progression of DILI, the gut commensal fungal component has not yet been functionally identified. Methods Mice were pretreated with fluconazole (FC) to deplete the gut commensal fungi and were then subject to acetaminophen (APAP) gavage. In addition, transcriptome sequencing was performed to identify differentially expressed genes (DEGs) between control and fluconazole-pretreated groups of the mice challenged with APAP. Results Gut commensal fungi ablation through fluconazole pretreatment predisposed mice to APAP-induced hepatotoxicity, characterized by elevated serum liver enzyme levels and more severe centrilobular necrosis, which appears to be caused by robust inflammation and oxidative stress. The 16S rDNA sequencing results indicated that Akkermansia muciniphila abundance had significantly decreased in gut fungi-depleted mice, whereas increased abundance of Helicobacter rodentium was observed. The gene interaction network between DEGs identified by the transcriptome sequencing highlighted a significant enrichment of Cyp2a5 in the liver of APAP-treated mice that were preadministrated with fluconazole. Pharmacological inhibition of Cyp2a5 by 8-methoxypsoralen (8-MOP) could significantly attenuate hepatic inflammation and oxidative stress in mice, thereby conferring resistance to acute liver injury caused by APAP administration. Conclusions Our data highlighted the significance of gut commensal fungi in hepatic inflammation and oxidative stress of APAP mice, shedding light on promising therapeutic strategies targeting Cyp2a5 for DILI treatment.